Measurements of lightning peak currents in the first return stroke of negative cloud to ground flashes - Weerasekera, A.B.; Sonnadara, D.U.J.; Fernando, I.M.K.; Lelwala, R.; Ariyaratne, T.R.; Liyanage, J.P. (My University, 2001)
Two lightning direction-finding stations were utilised in measuring the lightning ground flashes in and around Sri Lanka during the year 1999. By using 57 published triggered lightning data it has been shown that the peak currents at the source location can be estimated by using the range normalised signal strengths measured by the DF stations. The estimated errors in the peak currents vary exponentially with the distance between the strike location and DF station site and have a maximum error of 2.5 kA within their nominal range of 400 km. The peak current measurements are sensitive to the attenuation due to finite conductivity of ground and hence depend on the range at which the measurements are conducted. The calculated average lightning peak current values found to be in the range of 10-250 km and 20-120km are, 38 kA and 27 kA respectively for Sri Lanka in the tropics which agrees well with the past measurements done in other countries.
Keywords: lightning peak currents; cloud; flashes